THE EFFECT OF IRRADIATION OF THE LIQUID PHASE WITH NANOSECOND ELECTROMAGNETIC PULSES ON CRYSTALLIZATION AND STRUCTURE FORMATION, PROPERTIES OF COPPER AND TIN BRONZE - E. H. Ri; Hosen Ri; S. V. Dorofeev; A. S. Zhiventiev; T. S. Zhernova; G. A. Knyazev (Литьë и металлургия)
Complex research of influence of duration of liquid phase irradiation by electromagnetic impulses on parameters of liquid state parameters is carried out.